The Effect of Using Reverse Classroom Strategy on Learning Offensive Skills in Basketball for Students - Muayad, Mustafa; Omar, Saadi (Journal of Physical Education, 2022)
The research aimed at identifying the effect of revers classroom strategy on learning some offensive skills in basketball for students as well as comparing this strategy with the traditional style in learning some offensive skills in basketball. The researchers used the experimental program on (36) sophomore college of physical education and sport sciences students/ university of Dihok 2021- 2022. The subjects were dividing into two equal groups and the experimental group followed a 12-teaching session program for (6) weeks. The data was collected and treated using SPSS to conclude that there are significant differences (0.05) in learning dribbling with changing direction in favor of the experimental group.